Survival following sublobar resection after neoadjuvant therapy for T1N1-2M0 lung cancer - Hayley Reddington; Isabel Emmerick; Javier Diaz Collante; Aniket Maini; Raghav Kanzaria; Allison Crawford; William Phillips; Mark Maxfield; Karl Uy; Feiran Lou (PLoS ONE, 2026)
Background Lobectomy remains the standard surgical approach for resectable non-small cell lung cancer (NSCLC), but sublobar resection is increasingly considered, particularly for small, early-stage tumors. The role of sublobar resection after neoadjuvant therapy is unclear. We compared survival after sublobar resection versus lobectomy among patients with T1N1-2M0 NSCLC treated with neoadjuvant therapy. Methods Using the National Cancer Database (2011–2021), we identified patients ≥18 years with clinical stage T1N1-2M0 NSCLC who received neoadjuvant chemotherapy, chemoradiation, or chemoimmunotherapy followed by resection within 8 months. Patients with pneumonectomy, metastases, positive margins were excluded. Patients were grouped by resection type: sublobar (wedge or segmentectomy) vs. lobectomy (including bilobectomy and extended). Survival was assessed via Kaplan–Meier analysis and multivariable Cox regression. Results Of 2,257 patients, 148 (6.6%) underwent sublobar resection. Compared to lobectomy, sublobar resection was associated with fewer lymph nodes examined (24% vs. 54% with >10 nodes, p < 0.001) and shorter hospital stays (3.9 vs. 5.3 days, p < 0.001). Stage distribution was similar. One-year survival was comparable for both groups in stage II and III disease. At 5 years, survival was lower for stage III patients undergoing sublobar resection (48.6% vs. 59.9%, p < 0.01), with adjusted analysis confirming worse survival (HR = 1.41, p = 0.013). Conclusions Among patients with T1N1-2M0 NSCLC treated with neoadjuvant therapy, sublobar resection was associated with similar short-term but inferior long-term survival compared to lobectomy. Lobectomy remains preferred for patients with adequate reserve, though sublobar resection may be appropriate for select patients.